Development and investigation of gastro retentive dosage form of weakly basic drug - Shah, Samip S; Pandya1, Shridhar J; Waghulade, Mahesh K (Asian Journal of Pharmaceutics (AJP), 2014)
The release of drug substance from controlled-release dosage forms is often pH-dependent since most drugs are either weak acids or weak bases. A system that permits the drug release to be changed freely while maintaining pH-independent drug release (model drug was Domperidone) was developed. Powder mixture of drug and HPMC K4M, eudragit L100, sodium bicarbonate (as gas-generating agent) and other excipients were mixed and directly compressed using single-punch tablet compression machine. It was found that sodium bicarbonate reacts with HCl and produce carbon dioxide which creates pores in tablet and elevates swelling by wetting the polymer. So it helps in maintaining the buoyancy. The release rate could be modified by varying the polymer ratio. The prepared tablets were evaluated for general appearance, content uniformity, hardness, friability, buoyancy, in vitro drug release and in vivo studies.The best formulation (D1) was selected based on in vitro characteristics and was used in vivo radiographic studies by incorporating BaSO4. These studies revealed that the tablets remained in the stomach for 250630 min in fasted rabbits and indicated that gastric retention time was increased by the floating principle, which was considered desirable for the absorption window drugs. The linear regression analysis and model fitting showed that all these formulations followed Higuchi model, which had a higher value of correlation coefficient(r). The scanning electron microscopy images of the tablet (D1 formulation) were taken before and after dissolution and images showed that the drug was released from matrix by diffusion mechanism. Stability studies of all formulations were carried out at elevated temperature and humidity conditions of 4062oC/7565% RH and a control sample was placed at an ambient condition for 12 months. It was found that there was no significant change in buoyancy property as well as in drug content from initial drug content of all the formulations at the end of 12 months, indicating that the formulations are stable.